Computational analysis of the early stage of cuprous oxide sulphidation: a top-down process. (28th April 2017) - Stenlid, J. H.; Johansson, A. J.; Leygraf, C.; Brinck, T.
ABSTRACT: The initial steps of Cu2 O sulphidation to Cu2 S have been studied using plane-wave density functional theory at the PBE-D3+U level of sophistication. Surface adsorption and dissociation of H2 S and H2 O, as well as the replacement reaction of lattice oxygen with sulphur, have been investigated for the most stable (111) and (100) surface facets under oxygen-lean conditions. We find that the (100) surface is more susceptible to sulphidation than the (111) surface, promoting both H2 S adsorption, dissociation and the continued oxygen–sulphur replacement. The results presented in this proceeding bridge previous results from high-vacuum experiments on ideal surface to more realistic corrosion conditions and set the grounds for future mechanistic studies. Potential implications on the long-term final disposal of spent nuclear fuel are discussed. This paper is part of a supplement on the 6th International Workshop on Long-Term Prediction of Corrosion Damage in Nuclear Waste Systems . GRAPHICAL ABSTRACT: